Identifying and Reducing Waste in the Chicken Carcass Production Process at PT. Ciomas Adisatwa - Izdihar, Ulfah; Kristanti, Novita Erma; Nurbaiti, Nurbaiti; Hapsarini, Indira; Saraswati, Ayu Rahayu (Agroindustrial Journal, 2024)
PT. Ciomas Adisatwa unit Berbah is one of the Poultry Slaughterhouses (PSh) in Yogyakarta, producing 2,000 chickens/hour. However, some production steps do not increase the value of the finished product. Because of that, wasteful and non-value-added production processes must be eliminated to reduce the risk of contamination in PSh products and make the production process more efficient. Therefore, this study aims to identify the causes of waste and find an appropriate system to reduce the waste process. The methods used in this study include the Value Stream Analysis Tools (VALSAT) technique and future state mapping. Lean manufacturing is a concept used to reduce or eliminate waste in a production process. The wastes identified in the PT Ciomas Adisatwa production process include waiting activity, inappropriate processing, and unnecessary motion. The material weighing process identified the waiting activity because it was waiting for the Delivery Order (DO). Inappropriate processing occurs in hair removal rework in a clean area. The third waste is unnecessary motion, movement that is not needed occurs in cutting operators and dirty processes. The proposed improvements to address these wastes include enhancing the integration of information flow systems using a computer network, adding a plucker machine, and clarifying the division of tasks for each workstation to avoid unnecessary motion.